Experienced inclusion and recognition amongst people with spinal cord injury: A comparative study in Norway, The Netherlands, and Australia - Annelie Schedin Leiulfsrud; Kristian Bernhof Ellinggard; Marcel W. M. Post; Mohit Arora; Håkon Leiulfsrud (PLoS ONE, 2025)
Background The aim of this article is to study inclusion and recognition experienced amongst people with a Spinal Cord Injury (SCI) in Norway, The Netherlands, and Australia. This is approached both from the perspectives of an interest in the impact of mobility limitations versus social attitudes, and from a consideration of differences between societies. Methods The data derive from the core questionnaire of International Spinal Cord Injury Community Survey with extended national modules on the attitudes and values of respondents from Norway, The Netherlands, and Australia. The data gathered in 2017–18 include 2,450 participants aged 18 years or older. The data are analysed and presented with descriptive statistics and OLS regression analyses. In order to explore our main questions, we run regression controlling for country effects in addition exploring within country effects. Results Mobility limitations are a substantially weaker predictor of self-perceived inclusion and recognition than experiences of negative attitudes towards disabled people. Stereotypical attitudes and norms in society are shown to have various impacts on inclusion in the three countries. The Norwegian respondents report overall better results on inclusion and recognition than respondents in Australia and The Netherlands, illustrating the importance of national contexts. Conclusions Challenges associated with inclusion, recognition, and respect after SCI need to be defined in a language broader than mobility limitations and stereotypical attitudes towards people with an SCI. The main road to both inclusion and recognition in society is primarily linked to job and educational status, in addition to family and friends. The results are of particular interest as measures to support reintegration into society, including a strengthening of labour market integration programs.